2005
DOI: 10.1097/01.ccm.0000152224.01949.01
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acquired infections in intubated patients with the combination of two decontamination regimens

Abstract: Acquired infections were substantially reduced by mupirocin/chlorhexidine plus polymyxin/tobramycin, whereas each regimen given alone was ineffective. Whether both regimens could increase Candida infections deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 33 publications
1
96
0
Order By: Relevance
“…The therapy for extraintestinal E. coli infections does consist of antibiotics. However, antibiotics have the disadvantage of adverse effects, safety problems during pregnancy and selective pressure that can induce the emergence of resistant strains (Camus et al 2005;Vincent 2003). The rates of antibiotic resistance among E. coli strains have increased greatly over the past two decades, encouraging the search for novel antimicrobial strategies (Nickel 2007;Moreno et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The therapy for extraintestinal E. coli infections does consist of antibiotics. However, antibiotics have the disadvantage of adverse effects, safety problems during pregnancy and selective pressure that can induce the emergence of resistant strains (Camus et al 2005;Vincent 2003). The rates of antibiotic resistance among E. coli strains have increased greatly over the past two decades, encouraging the search for novel antimicrobial strategies (Nickel 2007;Moreno et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We were not tracking catheter-associated urinary tract infection rates in the preintervention period. However, for units with high rates of any of these infections, CHG bathing provides a reasonable intervention to reduce such infections, 4,[22][23][24][25][26][27] although not all studies showed reductions in infection rates. 28 Compliance with nasal swab screening and hand hygiene are essential measures to analyze the impact of CHG bathing.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after that study, many hospitals decided to abandon bath basins for ICU bathing in favor of using washcloths impregnated with 2% CHG. Historically, several studies 11,[15][16][17][18][20][21][22]27 of the effects of CHG bathing used 4% CHG in bath basins or showering; other studies 4,10,[12][13][14][23][24][25][26]28 used cloths impregnated with 2% CHG. Our surgical/ burn/trauma ICU staff nurses willingly tried the CHGimpregnated cloths before this study but were not satisfied with their performance and preferred the bath-basin method for patient bathing. Since the report of bath basin contamination by Johnson et al, 3 Powers and colleagues 31 studied the presence of bacterial contaminants in wash basins when CHG solution was used in place of standard soap and water to wash patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations